Using Digital Mind Mapping with Microsoft 365 to Improve Student’s Creative Thinking on Biology - Maesaroh Maesaroh; Jannah Firdausi; Eka Kartikawati; Irdalisa Irdalisa; Mega Elvianasti (Jurnal Penelitian Pendidikan IPA, 2023)
Creative thinking skills are one of the 21st-century life skills. The development of students’ creative thinking skills is important as a learning goal. However, learning in schools still tends to prioritize short-term learning outcomes on product dimensions only. The mind mapping method in blended learning activities with the help of Microsoft 365 provides space for students to develop their creativity. This study aims to develop students' creative thinking skills through the Microsoft 365-based mind mapping method. A total of 68 students from public high schools in Jakarta were sampled in this experimental study. The results showed that there was an increase in the indicators of students' creative thinking in the experimental class on indicators of originality of 70.3%, flexibility of 61.3%, fluency of 30%, and better than the control class. Microsoft 365-based mind mapping learning can be used as an alternative in creating a learning atmosphere that develops creative thinking skills because students have the authority to arrange concepts to be conveyed by choosing words that represent concepts, through colors and appropriate forms of symbols. with student creativity. Microsoft 365 has features that can facilitate interaction in class, as well as reach individual student needs through the personalized section in the one-note feature. Other features, such as Microsoft Sway, Microsoft Forms, and Microsoft PowerPoint 365 provide full support for classroom learning interactions with the mind mapping method